Exploration of the Role of Game Theory in Increasing the Effectiveness of Competition Law Enforcement and the Reality of Its Implementation in the Field - Noeri, Irsyad; Soesatyo, Bambang (Pelopor Publikasi Akademika, 2025)
Competition law enforcement is a critical instrument in creating a healthy and competitive market climate. In this context, game theory serves as an analytical framework to map strategic interactions between business actors, particularly in cases involving collusion, cartels, and other anti-competitive behaviors. This study explores the extent to which game theory has been implemented in Indonesia’s competition law enforcement, covering the investigation, evidence-gathering, and decision-making processes. By using a normative and juridical-empirical approach, this study reveals a gap between the theoretical potential of game theory and its limited practical application due to regulatory constraints, institutional capacity, and lack of technical expertise among law enforcers. The findings emphasize the importance of aligning economic theory with legal instruments to improve the effectiveness of competition law enforcement. As a strategic recommendation, the study suggests strengthening institutional capabilities through specialized training, issuing technical guidelines on economic analysis, enhancing data transparency, and promoting stronger collaboration between regulators and academia to ensure broader integration of game theory in practice.